Nuclear theory and energy - Jay, David (Chicago : Encyclopaedia Britannica Educational Corporation, 1985)
Describes atomic nucleus reactions which release energy and thereby change the structure of matter itself. Tells how the radioactivity, nuclear fission, and nuclear fussion which arise from these reactions educate, benefit, and endanger humankind.
Keywords: Nuclear energy; Nuclear reactions; Matter -- Constitution